Comparison of left versus right atrial myocardium in patients with sinus rhythm or atrial fibrillation – an assessment of mitochondrial function and microRNA expression. Issue 8 (August 2014) - Slagsvold, Katrine Hordnes; Johnsen, Anne Berit; Rognmo, Øivind; Høydal, Morten; Wisløff, Ulrik; Wahba, Alexander
Abstract Several of the cellular alterations involved in atrial fibrillation (AF) may be linked to mitochondrial function and altered microRNA (miR) expression. A majority of studies on human myocardium involve right atrial (RA) tissue only. There are indications that AF may affect the two atria differentially. This study aimed to compare interatrial differences in mitochondrial respiration and miR expression in the RA versus left atrium (LA) within patients with sinus rhythm (SR) and AF. Thirty‐seven patients with AF (n = 21) or SR (n = 16), undergoing coronary artery bypass surgery and/or heart valve surgery, were included. Myocardial biopsies were obtained from RA and LA appendages. Mitochondrial respiration was assessed in situ in permeabilized myocardium. MiR array and real‐time quantitative polymerase chain reaction were performed to evaluate miR expression. Mitochondrial respiratory rates were similar in RA versus LA. Expression of miR‐100, ‐10b, ‐133a, ‐133b, ‐146a, ‐155, ‐199a‐5p, ‐208b, and ‐30b were different between the atria in both SR and AF patients. In contrast, differential expression was observed between RA versus LA for miR‐93 in patients with SR only, and for miR‐1, ‐125b, ‐142‐5p, ‐208a, and ‐92b within AF patients only. These results indicate that mitochondrial respiratory capacity is similar in the RA and LA of patients with SR and AF. Differences in miR expressional profiles are observed between the RA versus LA in both SR and AF, and several interatrial differences in miR expression diverge between SR and AF. These findings may contribute to the understanding of how AF pathophysiology may affect the two atria differently.